Kineanthropometric profile of weightlifters of different age and gender categories in the Coquimbo region. (Revista horizonte, 2022)
The Kineanthropometric profile allows identifying characteristics of the athlete or sports discipline, being an efficient tool in the monitoring and control of training due to its usefulness, validity and low cost.Objective: To describe the kineanthropometric profile in Olympic weightlifters: adolescents and adults of both sexes, representatives in regional and national competitions in the Coquimbo region.Methods: A kineanthropometric recording was carried out, mainly somatotype and 5 body components.Results: It allows us to know the somatot ype and body composition values for adults and adolescents of both sexes of regional weight lifting.Conclusion: The kineanthropometric profile of the local weightlifter allows us to adjust the training according to our conditions and the necessary strateg ies to achieve the expected results.